Impairment of nuclear F-actin formation and its relevance to cellular phenotypes in Hutchinson-Gilford progeria syndrome. Issue 1 (1st January 2020) - Takahashi, Yuto; Hiratsuka, Shogo; Machida, Nanako; Takahashi, Daisuke; Matsushita, Junpei; Hozak, Pavel; Misteli, Tom; Miyamoto, Kei; Harata, Masahiko
ABSTRACT: Hutchinson-Gilford progeria syndrome (HGPS) is a premature aging disorder caused by a mutation of lamin A, which contributes to nuclear architecture and the spatial organization of chromatin in the nucleus. The expression of a lamin A mutant, named progerin, leads to functional and structural disruption of nuclear organization. Since progerin lacks a part of the actin-binding site of lamin A, we hypothesized that nuclear actin dynamics and function are altered in HGPS cells. Nuclear F-actin is required for the organization of nuclear shape, transcriptional regulation, DNA damage repair, and activation of Wnt/β-catenin signaling. Here we show that the expression of progerin decreases nuclear F-actin and impairs F-actin-regulated transcription. When nuclear F-actin levels are increased by overexpression of nuclear-targeted actin or by using jasplakinolide, a compound that stabilizes F-actin, the irregularity of nuclear shape and defects in gene expression can be reversed. These observations provide evidence for a novel relationship between nuclear actin and the etiology of HGPS.